Operative Complications and Outcomes Comparing Small and Large Uterine Weight in Case of Laparoscopic Hysterectomy for a Benign Indication - Lambat Emery, Shahzia; Boulvain, Michel; Petignat, Patrick; Dubuisson, Jean (Frontiers in Surgery, 2021)
Study Objective: This study was performed to evaluate the association between uterine weight and operative outcomes in women undergoing laparoscopic hysterectomy for a benign indication. Methods: This is a secondary analysis of a randomized trial with data collected prospectively and retrospectively. The data of 159 women undergoing laparoscopic hysterectomy for a benign indication were analyzed. Women were divided in two groups according to the postoperative uterine weight: small uterus group (<250 grams) and large uterus group (≥250 grams). Operative complications were compared between the two groups. Operative outcomes (need for uterine morcellation, operative duration, estimated blood loss), postoperative pain, and hospital length of stay were also analyzed. Main Results: Operative complications were not significantly different between the two groups (37% in the large uterus group versus 41% in the small uterus group). Operative outcomes showed a significantly increased use of uterine morcellation in the large uterus group (61% in the large uterus group versus 10% in the small uterus group). The operative duration was 150 min in the small uterus group and 176 min in the large uterus group, which corresponds to an increase of 17% in the large uterus group. The mean pain score on the day of surgery was identical in both groups (VAS pain score 5), but significantly in favor of the large uterus group on day 1 postoperatively (VAS pain score 4 in the small uterus group and 3 in the large uterus group). There was no statistical difference between groups in the mean hospital stay (62 ± 37 hours in the small uterus group versus 54 ± 21 hours in the large uterus group). In terms of surgical indication, the small uterus group comprised more patients with endometriosis/adenomyosis (36%) and the large uterus group more patients with leiomyoma (93%). Conclusion: The results from this study show that, even if a large uterine weight is associated with increased uterine morcellation requirement and operative duration, a laparoscopic approach is safe and does not increase operative complications nor pain and/or length of hospital stay in women undergoing hysterectomy for a benign indication.